Equivalent linear algebraic expressions

# Equivalent linear algebraic expressions

#### Question 1

Which expression is equivalent to 2 − 3t ?

a | 3 − 2t | b | 3t − 2 | c | −2 + 3t | d | −3t + 2 |

#### Solution

The linear expression 2 − 3t can be thought of as the sum of two terms: 2 and − 3t.

That is, 2 − 3t = 2 + (−3t ).

The order of addition does not matter.

2 + (−3t ) = (−3t ) + 2 for all values of t.

You do not need the brackets in this second expression.

2 + (−3t ) = −3t + 2 for all values of t.

So we can say 2 + (−3t ) is equivalent to −3t + 2.

So the answer is d.

You can do a check of your answer by substituting in a value for t. No matter what value you choose, **equivalent expressions** will always give the **same** answer. It must be true for every number you substitute.

For example, let t = 1.

Then 2 − 3t = 2 − 3 = −1

and −3t + 2 = −3 + 2 = −1.

Consider one more.

Let t = 2.

Then, 2 − 3t = 2 − 6 = −4

and −3t + 2 = −6 + 2 = −4.

© Australian Mathematical Sciences Institute, except where indicated otherwise. This material is licensed under a Creative Commons Attribution-NonCommercial 3.0 Unported (CC BY-NC 3.0) licence http://creativecommons.org/licenses/by-nc/3.0/